1988
DOI: 10.1115/1.3261717
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Crack Face Friction and Trapped Fluid on Surface Initiated Rolling Contact Fatigue Cracks

Abstract: A two-dimensional model of a surface initiated rolling contact fatigue crack has been developed. The model takes into account the effects of frictional locking between the faces of the crack, and the influence of fluid pressure acting on the crack faces. The model has been used to investigate three possible mechanisms for propagating the cracks: mode II crack growth due to the cyclic shear stresses caused by repeated rolling contact; crack growth due to fluid forced into the crack by the load; and crack growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
205
0
6

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(225 citation statements)
references
References 0 publications
14
205
0
6
Order By: Relevance
“…can ÒunlockÓ mode II growth through helping to overcome crack face friction [18]. In the current results high values of mode II are predicted even with almost zero K I at the right tip, although larger K I values are predicted at the left.…”
Section: Stress Intensity Factor Dependence On Crack Sizementioning
confidence: 52%
“…can ÒunlockÓ mode II growth through helping to overcome crack face friction [18]. In the current results high values of mode II are predicted even with almost zero K I at the right tip, although larger K I values are predicted at the left.…”
Section: Stress Intensity Factor Dependence On Crack Sizementioning
confidence: 52%
“…16a). The friction coefficient of crack faces has a vital effect on the crack propagation and the propagation is unlikely when the value is above 0.2 [32]. Furthermore, the crack growth decreases with an increase in the friction coefficient of the crack face.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hourlier and Pineau applied a criteria under non-proportional conditions where the crack path corresponds to the direction where the mode I fatigue growth rate is maximum [32]. Bower suggested that the crack would tend to propagate in the direction of the maximum value of ∆σ max [33]. Lamacq showed that for fretting fatigue conditions, the K II = 0 approach worked well to predict the crack angle [26].…”
Section: Life Predictionsmentioning
confidence: 99%